The Internal Control And Financial Statements As Moderating Of Ethical Climate - Xaverius M Y Janwarin; I Made Narsa (Jurnal Akuntansi, 2022)
This study aims to analyze the effect of the government's internal control system on the government of financial statements quality with the moderating role of the ethical climate of the organization. The survey method was conducted on 80 employees of the planning and finance division of the Maluku Provincial Government who participated in this study. Research data in the form of survey questionnaires were collected and analyzed using smart PLS. The results of this study indicate that the government's internal control system and ethical climate of the organization have a positive and significant effect on the government of financial statements quality. The variable of the government's internal control system has a positive and significant effect on the ethical climate of the organization. The ethical climate of the organization variables can moderate the effect of the government's internal control system on the government of financial statements quality in a positive and significant way.